Human trafficking in Egypt: policy and alternatives? - Guirguis, Bernadette Michel (AUC Knowledge Fountain, 2012)
This thesis attempts to analyze the issues associated with human trafficking in context to relevant policies and possible alternatives in Egypt. This growing industry is based on Egypt's strategic location, and it has raised several concerns, as a growing number of individuals are being forced into marriages, prostitution, labor, and organ trading. The main research question is: how effective are the Egyptian government policies to combat the human trafficking and in what areas could they be improved. Thus, this calls for the immediate attention of policy makers. It has been identified in this paper that better governance and administrative policies can improve and abate this problem. Some other factors that can help control the situation are an increased awareness among the Egyptian populace, establishment of stringent policies and adherence to them, and better border control practices. This paper has used reviewed secondary literature on this subject and accumulated the understanding from several interviews with victims to show the manner in which the human trafficking business in Egypt can be curbed and eliminated.